"u=X(x)*T(t)\\\\\n\\dfrac{T'}{\\beta T}=\\dfrac{X'}{X}=const=-\\lambda\\\\\nX''+\\lambda X=0\\\\\nX(x)=C_1\\cos(\\sqrt{\\lambda}x)+C_2\\sin(\\sqrt{\\lambda}x)\\\\\nX(0)=C_1*1+C_2*0=C_1=0=>X(x)=\\sin(\\sqrt{\\lambda}x)\\\\\nX(L)=\\sin(\\sqrt{\\lambda}L)=0\\\\\n\\sqrt{\\lambda}L=\\pi *k=>\\lambda=(\\dfrac{\\pi *k}{L})^2\\\\\nX(x)=\\sin(\\sqrt{\\lambda}x),\\\\\nT(t)=C*e^{-\\beta\\lambda t},\n\\lambda=(\\dfrac{\\pi *k}{L})^2=>\\\\\nWe \\space know \\space that \\space:u=X(x)*T(t), \\space so\\\\\nu(x,t)=\\underset{k=0}{\\sum}C*e^{-\\beta\\lambda t}*\\sin(\\sqrt{\\lambda}x),\\\\\nwhere\\\\\nC=\\dfrac{2}{L}\\overset{L}{\\underset{0}{\\int}}f(x)*\\sin(\\sqrt{\\lambda}x)dx,is \\space coefficient \\space of \\space a \\space Fourier \\space series\\\\\n\\lambda=(\\dfrac{\\pi *k}{L})^2"
Comments
Leave a comment